2021
DOI: 10.1007/s10238-021-00716-w
|View full text |Cite
|
Sign up to set email alerts
|

Different spatial distribution of inflammatory cells in the tumor microenvironment of ABC and GBC subgroups of diffuse large B cell lymphoma

Abstract: Diffuse Large B-Cell Lymphoma (DLBCL) presents a high clinical and biological heterogeneity, and the tumor microenvironment chracteristics are important in its  progression. The aim of this study was to evaluate tumor T, B cells, macrophages and mast cells distribution in GBC and ABC DLBCL subgroups through a set of morphometric parameters allowing to provide a quantitative evaluation of the morphological features of the spatial patterns generated by these inflammatory cells.   Histological ABC and GCB samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…We also found immune composition differences between the two DLBCL cell-of-origin (COO) subtypes. Relative to GCB subtype samples, ABC subtype samples are more enriched for CD68−CD163+ mac-rich CNCs ( p = 0.008), while GCB samples have fewer immune-rich CNCs and more immune-sparse CNCs, which is in line with previously published data [ 9 ]. Additionally, when contrasting spatial context between ABC vs. GCB subtype, we find that the CD8-rich CNCs in ABC are more proximal to the CD68−CD163+ mac-rich ( p = 0.002) and DC-rich ( p = 0.02) CNCs (Fig.…”
Section: To the Editorsupporting
confidence: 91%
“…We also found immune composition differences between the two DLBCL cell-of-origin (COO) subtypes. Relative to GCB subtype samples, ABC subtype samples are more enriched for CD68−CD163+ mac-rich CNCs ( p = 0.008), while GCB samples have fewer immune-rich CNCs and more immune-sparse CNCs, which is in line with previously published data [ 9 ]. Additionally, when contrasting spatial context between ABC vs. GCB subtype, we find that the CD8-rich CNCs in ABC are more proximal to the CD68−CD163+ mac-rich ( p = 0.002) and DC-rich ( p = 0.02) CNCs (Fig.…”
Section: To the Editorsupporting
confidence: 91%
“…Treating B-lineage non-Hodgkin lymphoma (NHL) with chimeric antigen receptor T (CAR-T) is a typical application of this strategy [ 136 ]. Heterogeneous mutational spectrum and spatial distribution of several immune cell types have been observed in subsets of patients with diffuse large B-cell lymphoma [ 137 , 138 ]. However, by targeting CD19, which was constitutively expressed by almost all malignant cells in DLBCL, more than half of the patients obtained durable long-term response from the CAR-T cell infusion; much higher than the objective response rate of anti-PD-1 monotherapies on DLBCL [ 139 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, they showed that the presence of CD68positive tumor-infiltrating macrophages correlates with poor prognosis in the aggressive B-cell NHL subtype (7,8). Moreover, Guidolin et al (9) quantitatively evaluated the morphological features and spatial patterns (the percentage and position of positive cells in the tissue) of inflammatory cells (including macrophages) in the DLBC microenvironment. They used a morphological approach based on the estimation of an uniformity index and a spatial statistic approach that involved calculating the Ripley's K-function of the distances between cells (9).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Guidolin et al (9) quantitatively evaluated the morphological features and spatial patterns (the percentage and position of positive cells in the tissue) of inflammatory cells (including macrophages) in the DLBC microenvironment. They used a morphological approach based on the estimation of an uniformity index and a spatial statistic approach that involved calculating the Ripley's K-function of the distances between cells (9). Their found a significantly higher immune infiltrate and uniform distribution in the more aggressive ABC subtype than in the GBC subtype (where immune cells were clustered).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation